The Role of Positive Emotion in Mediating the Effect of Promotional Attractiveness toward Impulse Buying: A Study of GoFood Online Food Delivery Brand Customers in Denpasar City - Kadek Ayu Mayang Savitri; Gede Suparna (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
Gojek, as a leading on-demand service company in Indonesia, continues to leverage technological advancements and shifts in consumer behavior from offline to online shopping. One of its flagship services, GoFood, faces challenges in maintaining its market position and increasing the number of transactions due to increasing competition in the food delivery industry. This study aims to explain the role of positive emotions in mediating the influence of promotional appeals on impulse purchases among GoFood customers. This study uses consumer behavior theory and the Stimulus-Organism-Response (S-O-R) model as a theoretical basis. The study was conducted in Denpasar City, involving 180 respondents through a survey method using questionnaires distributed offline and online. The sampling technique used was non-probability sampling with a purposive sampling approach. Data analysis was carried out using path analysis, classical assumption tests, Sobel tests, and Variance Accounted For (VAF) tests with the help of SPSS 25 software. The results showed that all proposed hypotheses were accepted. Promotional appeals had a positive and significant effect on impulse purchases. Promotional appeals also had a positive and significant effect on positive emotions. Furthermore, positive emotions also significantly influence impulse buying. Positive emotions have been shown to partially mediate the effect of promotional appeal on impulse buying. Practical implications of this research suggest that GoFood optimize attractive discount promotions by providing users with greater flexibility and control to evoke positive emotions that encourage impulse buying behavior. Discount promotions should be designed creatively and personally, using engaging visuals, persuasive language, and offers tailored to customer preferences.